In vivo Pharmacokinetic/Pharmacodynamic (PK/PD) Profiles of Tulathromycin in an Experimental Intraperitoneal Haemophilus parasuis Infection Model in Neutropenic Guinea Pigs - Guo, Li-li; Gao, Rui-yuan; Wang, Li-hua; Lin, Shu-jun; Fang, Bing-hu; Zhao, Yong-da (Frontiers in Veterinary Science, 2021)
Tulathromycin is a semi-synthetic macrolide antimicrobial that has an important role in veterinary medicine for respiratory disease. The objective of the study was to develop a pharmacokinetic/pharmacodynamic (PK/PD) model to examine the efficacy and determine an optimal dosage of tulathromycin intramuscular (IM) treatment against Haemophilus parasuis infection induced after intraperitoneal inoculation in neutropenic guinea pigs. The PKs of tulathromycin in serum and lung tissue after intramuscular administration at doses of 1, 10, and 20 mg/kg in H. parasuis-infected neutropenic guinea pigs were evaluated by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The tulathromycin minimum inhibitory concentration (MIC) against H. parasuis was approximately 16 times lower in guinea pig serum (0.03 μg/mL) than in cation-adjusted Mueller-Hinton broth (CAMHB) (0.5 μg/mL). The ratio of the 168-h area under the concentration-time curve (AUC) to MIC (AUC168h/MIC) positively correlated with the in vivo antibacterial effectiveness of tulathromycin (R2= 0.9878 in serum and R2= 0.9911 in lung tissue). The computed doses to achieve a reduction of 2-log10 CFU/lung from the ratios of AUC72h/MIC were 5.7 mg/kg for serum and 2.5 mg/kg for lung tissue, which lower than the values of 13.2 mg/kg for serum and 8.9 mg/kg for lung tissue with AUC168h/MIC. In addition, using as objective a 2-log10 reduction and an AUC0-72h as the value of the PK/PD index could be more realistic. The results of this study could provide a solid foundation for the application of PK/PD models in research on macrolide antibiotics used to treat respiratory diseases.